User Interface Usability of Mamat Adventure: The Study of Usability User Interface of Mamat Adventure Edugame Based on Heuristic Evaluation - Apong Suryani; Alvanov Z. Mansoor (Bina Nusantara University, 2022)
A game is a form of entertainment determined by a rule and conflict resolution by the player. A good game can display attractive visuals, make the player get engaged, and feel the needed pleasure. Visual is a medium that only concerns the sense of sight while the other senses like the sense of hearing (sound) cannot be included in the visual use Visual in a game is a part of the user interfaces. The user interface is a medium between a system and the user. The Ministry of Education and Culture of the Republic of Indonesia has released various free website-based edugames that can be accessed and played by Indonesia especially elementary school students. Mamat Adventure is one of the edugames provided by the Indonesian Ministry of Education and Culture. This theoretical exploration has begun with a discussion about the visual appearance related to the user interface in the edugame of Mamat Adventure. This analysis uses the Heuristic Evaluation method initiated by Jakob Nielsen and Rolf Molich to measure the effectiveness of the user interface in the game Mamat Adventure